Quantifying wrist angular excursion on impact for Jab and Hook lead arm shots in boxing - Gatt, I.; Allen, T.; Wheat, J. (Sports Biomechanics, 2021)
The hand region is reported as the most common injury site in boxing, with more observed time loss than any other area in this sport. The amount of wrist motion, specifically flexion, has been described as contributing to these injuries, yet no literature is available to quantify wrist kinematics in boxing. This is the first paper describing wrist motion on impact in boxing. Utilising an electromagnetic tracking system, two types of shots were assessed, Jab (straight arm) and Hook (bent arm), during in-vivo testing procedures with 29 elite boxers. For both shots, flexion and ulnar deviation occurred concurrent on impact, with an M and SD of 9.3 ± 1.9° and 4.7 ± 1.2° respectively for Jab shots, and 5.5 ± 1.1° and 3.3 ± 1.1° respectively for Hook shots, supporting dart throwing motion at the wrist. For both Jab & Hook, wrist motion on impact occurred within >30% and >20% respectively of total available active range of motion, with wrist angles greater in both flexion (t = 9.0, p < 0.001, d = 1.7) and ulnar deviation (t = 8.4, p < 0.001, d = 1.6) for Jab compared to Hook shots. The study provides novel and quantifiable information regarding wrist kinematics during the impact phase of punching and potentially an improved understanding of injury mechanisms in boxing.